PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER DENGAN ALAT PERAGA MATERI BANGUN RUANG KUBUS DAN BALOK PADA PESERTA DIDIK SMP DARUL ULUM MUNCAR - Mekar Arum Kusuma (Universitas Islam Malang, 2019)
This classroom action research was motivated by the low ability of students in terms of understanding concepts and problem solving abilities. The purpose of this study was to describe the application of the Number Head Together learning model with teaching aids to improve concept understanding and problem-solving abilities on the subject matter of building cubes and block of class VIII-C students of Darul Ulum Middle School 2017/2018 academic year held on April 16, 2018 to 9 May 2018. The type of research used was classroom action research with 2 cycles, consisting of 3 meetings in each cycle. The stages of each cycle include planning, implementation, observation and reflection. The data collection techniques and tools in this study used descriptive analysis techniques for data in the form of student work documents, lists of values and observations. The results showed that with the Number Head Together cooperative learning model with teaching aids there was a conducive learning atmosphere so that the ability to understand concepts and students' problem solving abilities increased, from the results of the study, it was known that the first cycle to the second cycle had an increase in the learning cycle. students reached 66.6% while in the second cycle there was an increase with a percentage of success reaching 86.6%. It was concluded that the NHT learning model could improve concept understanding and problem solving abilities.